Pl-mediated Transduction of a Gene That Controls Radiation Sensitivity and Capsular Polysaccharide Synthesis from Shigella dysenteriae to Escherichia coli - Markovitz, Alvin (1968)
When Shigella dysenteriae strain 60 is used as a donor and Escherichia coli K-12 strains that are ultraviolet (UV)-sensitive, mucoid, and proline-requiring (Pro(−)) are employed as recipients, selection for Pro(+) yields 2 to 6% nonmucoid clones. All of the nonmucoid clones examined are UV-resistant. Most of the nonmucoid UV-resistant transductants are partial diploids for the genes being studied. When these Shigella-Escherichia hybrids are used as donors with the same E. coli recipients, the cotransduction of Pro(+) and nonmucoidness is greatly increased (59 to 94% cotransduction). All of these nonmucoid transductants examined were also UV-resistant. The results indicate that Shigella contains an allele (designated ShproC(+)) homologous to proC of E. coli and a second linked allele (designated ShcapR(+)) homologous to the capR allele of E. coli. The ShcapR(+) allele changes the phenotype of certain E. coli strains from mucoid UV-sensitive (capR6) or very sensitive (capR9) to nonmucoid and UV-resistant. Unanticipated capR allele interactions in the partial diploid hybrids are described.